The Dynamic Relationship between Stock Market and Macroeconomy at Sectoral Level: Evidence from Chinese and US Stock Market. (8th March 2021) - Jin, Zhenni; Guo, Kun
Abstract : As a most important component of capital market, stock market has always been regarded as the "barometer" of macroeconomy. However, many researchers have found that the stock market is not always in the lead, especially for the emerging markets, and the leading role of different sector indices is also different for the corresponding sectors. From the perspective of a comparison between mature market and emerging market at sectoral level, this paper utilizes the thermal optimal method to examine the dynamic lead-lag relationships between stock sector indices and macroeconomic variables for the USA and China. The results show that, for the US stock market, three sector indices including consumption, industry, and real estate have been leading the corresponding macroeconomic variables since 2013; for the Chinese stock market, the lead-lag relationships are different for these sectors. The real estate sector index and the industry sector index have been leading the corresponding macroeconomic variables since 2010, and the lead-lag relationship between the consumption sector index and the total retail sales is not always positive or negative, which means that the consumption sector index does not always lead the total retail sales. The empirical results confirm that the "barometer function" of immature stock market is still weak and easier to be disabled by factors such as irrational market sentiment.